Global pattern of cardiovascular disease management in patients with cancer and impact of COVID-19 on drug selection: IRAQ—IC-OS survey-based study - Farhan, Hasan Ali; Yaseen, Israa Fadhil; Alomar, Mohammed; Lenihan, Daniel; Dent, Susan; Lyon, Alexander R. (Frontiers in Cardiovascular Medicine, 2022)
Background Regional variations in cardiovascular disease (CVD) and CVD management are well known. However, there is limited information on geographical variations in the discipline of Cardio-Oncology, including both the nature of CVD in patients with cancer and its management. Furthermore, during the recent COVID-19 pandemic, CV care for patients was disrupted resulting in an unknown impact on cardio-oncology services. Objective The aim of this study was to identify the regional variations in the management of CVD among patients with cancer and the impact of the COVID-19 pandemic on the selection of cardiovascular drugs in cardio-oncology. Methods An online survey was conducted by the Iraq Chapter of the International Cardio-Oncology Society (IC-OS). The survey was shared with cardiologists and oncologists in all seven continents to identify whether regional variations exist in cardio-oncology daily practice. Results From April to July 2021, 140 participants responded to the survey, including cardiologists (72.9%) and oncologists (27.1%). Most of the respondents were from the Middle East (26.4%), North America (25%), Latin America and the Caribbean (25%), and Europe (20.7%). Baseline CV risk assessment in patients with cancer using the HFA/IC-OS score was reported in 75.7% of respondents (78.4% cardiologists and 68.4% oncologists). Hypertension was the most common CVD treated by the survey respondents globally (52.1%) unlike in Europe where heart failure was the most prominent CVD (51.7%). The blood pressure cutoff value to initiate hypertension management is >140/90 mmHg globally (72.9%), but in North America (48.6%) it was >130/80 mmHg. In the Middle East, 43.2% of respondents do not use cardioprotective medication. During the COVID-19 pandemic, 10.7% of respondents changed their practice, such as switching from prescribing ACEI to ARB. Apixaban is the main anticoagulant used in patients with cancer (32.9%); however, in cancer patients with COVID-19 infection, the majority used enoxaparin (31.4%). Conclusion More than three-quarters of cardiologists and oncologists responding to the survey are using HFA/IC-OS proformas. The survey showed regional variations in the management of CVD on different continents. The use of cardioprotective agents was limited in some regions including the Middle East. COVID-19 pandemic impacted daily practice on the selection and switching of cardiovascular drugs including ACEI/ARB and the choice of anticoagulants.